Biosensors: Printed Organic Transistors with Uniform Electrical Performance and Their Application to Amplifiers in Biosensors (Adv. Electron. Mater. 7/2015). (July 2015) - Fukuda, Kenjiro; Minamiki, Tsukuru; Minami, Tsuyoshi; Watanabe, Makoto; Fukuda, Takashi; Kumaki, Daisuke; Tokito, Shizuo
<x xml:space="preserve">Abstract</x> In article number 1400052, Kenjiro Fukuda, Shizuo Tokito, and co‐workers present results for printed organic thin‐film transistor arrays with a high degree of electrical performance and exceptional uniformity. These arrays allow for the fabrication of a differential amplifier in a biosensor for detecting immunoglobulin G and validate the potential use of printed electronic circuits in practical sensor applications.